Evolution of the nanostructure of CdS using solvothermal synthesis at different temperature and its influence on the photoactivity for hydrogen production. (20th July 2016) - Vaquero, F.; Navarro, R.M.; Fierro, J.L.G.
Abstract: Evolution of the nanostructure of CdS was studied on samples prepared by solvothermal synthesis from low (90 °C) to high temperature (190 °C). Physicochemical characterization of CdS samples have shown the evolution with solvothermal temperature of the CdS nanostructures from lamellar structures composed of many random arranged crystal lattices with short-range crystalline sizes formed at low temperature to the formation of highly crystalline rods and wires with higher diameter and length as the solvothermal temperature rises. Photocatalytic activity for H2 production has shown that the combination of CdS nanorods having low diameter with small CdS nanocrystals with strong confinement effect (CdS-SQE) produced at medium temperature strongly enhances the photoactivity compared to that obtained on crystalline CdS in form of rods or wires produced at higher solvothermal temperature. Graphical abstract: Highlights: Differences in the nanostructure of CdS depending on solvothermal temperature. Significant differences in the photoactivity of CdS depending on its nanostructure. Combination of CdS nanorods with CdS-SQE strongly enhances the photoactivity.